Dimensi Metrik pada Graf Bintang Kipas dan Graf Bunga Sepatu - Layinatu Khusniyatinna'im; Tri Tri Atmojo Kusmayadi; Titin Sri Martini (Limits: Journal of Mathematics and Its Applications, 2025)
Let be a connected graph with set of vertices and set of edges . The distance from two distinct vertices , denoted by , is the length of the shortest path from and in . Let be an ordered subset of . For any vertex , the representation of vertex with respect to is defined as k-ordered pairs . The set is said to be the resolving set of if every two vertices differ then . The basis of is the resolving set of with the smallest cardinality. The cardinality of the base is defined as metric dimension, and is denoted by . This research aims to find the metric dimension of fan star graph and hibiscus graph. The research method in this research is a literature study. The result of this research are as follow the metric dimension of the fan star graph are for and and for dan , then the metric dimension of the hibiscus gaph are for and for .